Highly effective Cu doped SrTiO3 as a cathode driven by oxygen vacancies and redox of Ti4+/Ti3+ and Cu2+/Cu+ for rechargeable alkaline zinc batteries - Zhang, Jia Jun; Christelle Wang, Pau Ping; Suresh, Sagadevan; Nurhidayatullaili, Muhd Julkapli; Lai, Sai Hin; Thomas Yang, Chung Kuang; Juan, Joon Ching (Elsevier B.V., 2024)
There is great demand for environmental concerns and explosion hazard batteries. Rechargeable alkaline zinc batteries (RAZBs) have gained significant attention due to their exceptional characteristics such as affordability, safety features, and high theoretical gravimetric capacity. However, practically RAZBs still exhibit poor capacities and limited rechargeability. In this study, copper-doped SrTiO3 (Cu-STO) was successfully synthesized via facile hydrothermal method to be used as a cathode in RAZBs. The capacity of RZABs has enhanced up to 208 mAh g−1 (0.2 A g−1) or 1.5 folds as compared to that of pristine SrTiO3. This is attributed to the presence of oxygen vacancies (Vö) which facilitate the activation of redox-active sites involving Ti4+/Ti3+ and Cu2+/Cu+ ions. Moreover, the fast ions diffusion and good conductivity enable high capacity and rechargeability. Thus, RAZBs showed good rechargeability even after 1000 cycles under 1 A g−1. This provides the underlying potential of Cu-STO as cathode in RAZBs.